The running of animal shelters by non-governmental organizations - Kruk, Emil (Studia Prawnoustrojowe, 2021)
The article is of a scientific research nature, and its main aim is to discuss selected problems regarding the operation of animal shelters by NGOs. It is worth noting at this point that the study is focused on the presentation of practical aspects of the issue. The research has been aimed primarily at resolving doubts about whether or not NGOs are required to obtain a permit to run a shelter for homeless animals and doubts regarding the legal nature of ‘agreements’ on the operation of animal shelters, concluded by NGOs with competent local government bodies. The findings made in this respect are complemented by comments on the recently proposed amendments to the Act of 21 August 1997 on the protection of animals, which provided for subjective restrictions involving the narrowing of the circle of entities authorized to run shelters for homeless animals and introduced requirements to be met by natural persons involved in running the shelters.